Epistemologi Pendidikan Islam di Indonesia sebagai Solusi Menjawab Tantangan Ilmu Pengetahuan dan Metode Ilmiah di Era 4.0 - Hapidin, Ahmad; Natsir, Nanat Fatah; Haryanti, Erni (Tarbawiyah Jurnal Ilmiah Pendidikan, 2022)
Critical Analysis of the Epistemology of Science (Theory of Knowledge and Scientific Methods) aims to realize the development of Islamic education in Indonesia, as a solution in answering the Challenges of Science and Scientific Methods in Era 4.0. So that in this study it is necessary to uncover and explore the views of Islamic reformers in responding to the Challenges of Science and Scientific Methods in Era 4.0. this study concluded that in terms of realizing the development of Islamic education in Indonesia, as a solution in answering the Challenges of Science and Scientific Methods in Era 4.0, it is necessary to adapt to the development of the existing era, and need renewable science, this is because science and methods Scientific research is 1) to parse, 2) to assist (supporters), in realizing the development of superior Islamic education through the arguments contained in the Qur'an and Hadith. A real example is the establishment of formal schools, from elementary school (elementary school) to Islamic boarding school-based universities that exist in Indonesia. In responding to the challenges of science and scientific methods in the 4.0 era, it is necessary to develop an Islamic Education methodology through an alternative paradigm of integralism in the religious sciences with non-religious sciences, which can be done by pesantren-based school institutions.